Blending the Material and the Digital: A Project at the Intersection of Museum Interpretation, Academic Research, and Experimental Archaeology - Caroline Jeffra; Jill Hilditch; Jitte Waagen; Tijm Lanjouw; Markus Stoffer; Laurien de Gelder; Myung Ju Kim (EXARC Journal)
The power of digital technologies to communicate archaeological information in a museum context has recently been critically evaluated (Paardekooper, 2019). A recent collaboration between members of the Tracing the Potter’s Wheel project, the 4D Research Lab, and the Allard Pierson Museum and Knowledge Institute illustrates the way that such collaborations can avoid or overcome a number of the pitfalls highlighted in that publication.